Applying an online game-based formative assessment in a flowchart-based intelligent tutoring system for improving problem-solving skills - Hooshyar D.; Ahmad R.B.; Yousefi M.; Fathi M.; Horng S.-J.; Lim H. (Elsevier Ltd, 2023)
Bayesian networks; Computer aided instruction; Computer games; Computer programming; Computer systems programming; Decision making; Education computing; Flowcharting; Internet; Students; Empirical investigation; Formative assessment; Game-based Learning; Intelligent tutoring system; Intelligent tutoring system (ITSs); Problem solving skills; Programming knowledge; Technology acceptance; Problem solving